2022
DOI: 10.1038/s41598-022-06256-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3-dimensional printing guide template and pointed lotus-style regulator in percutaneous pedicle screw fixation for thoracolumbar fractures

Abstract: This study aims to analysis the efficacy of the 3D printing percutaneous guide template in combination with the pointed lotus-style regulator in percutaneous pedicle screw fixation. 60 thoracolumbar fractures patients receiving percutaneous pedicle screw fixation (PPSF) were enrolled and randomly divided into 3 groups. Patients in Group A received traditional PPSF, while patients in Group B received PPSF with flat end lotus-style regulator and patients in Group C received PPSF with pointed lotus-style regulato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The PEEK CAGE can be safely inserted into the intervertebral space, with the size, orientation, and depth displayed on the navigation screen, thereby avoiding endplate injury and misplacement (Figures 5B,C). Many studies have reported percutaneous pedicle screw process injury to the spinal cord and nerve roots (23,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The PEEK CAGE can be safely inserted into the intervertebral space, with the size, orientation, and depth displayed on the navigation screen, thereby avoiding endplate injury and misplacement (Figures 5B,C). Many studies have reported percutaneous pedicle screw process injury to the spinal cord and nerve roots (23,29,30).…”
Section: Discussionmentioning
confidence: 99%